2022
DOI: 10.34006/jmbi.v11i2.524
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Interest: Entrepreneurship Education, Income Expectations and Creativity

Abstract: This research was conducted in order to find out how important the influence of entrepreneurship education, income expectations and creativity is partly on the interest in entrepreneurship in students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. The research was conducted using a quantitative approach and the population was students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya. Non-probability samples were taken using a purposive sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The interest in entrepreneurship among students has been observed to be influenced by factors such as entrepreneurship education, income expectations, and inventiveness (Chahine, 2022). There is a need to persist in the development of educational resources pertaining to entrepreneurship, offering practical guidance on entrepreneurial activities, fostering aspirations for lucrative earnings, and cultivating creativity in the generation of business concepts (Prasetya & Azizah, 2022).…”
Section: Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in entrepreneurship among students has been observed to be influenced by factors such as entrepreneurship education, income expectations, and inventiveness (Chahine, 2022). There is a need to persist in the development of educational resources pertaining to entrepreneurship, offering practical guidance on entrepreneurial activities, fostering aspirations for lucrative earnings, and cultivating creativity in the generation of business concepts (Prasetya & Azizah, 2022).…”
Section: Entrepreneurshipmentioning
confidence: 99%
“…The inclusion of entrepreneurship education is of notable importance in the cultivation of an entrepreneurial attitude, the acquisition of specialised skills and competencies, and the encouragement of entrepreneurial activities (Di Paola et al, 2023). According to research, it has been determined that there is a favourable impact on students' inclination towards entrepreneurship, their expectations regarding money, and their creative abilities (Prasetya & Azizah, 2022). Moreover, research has demonstrated a clear correlation between entrepreneurship education and the enhancement of self-efficacy and the cultivation of entrepreneurial ambitions (Masnun et al, 2023).…”
Section: Entrepreneurship Educationmentioning
confidence: 99%